Self-confidence for emergency intervention: adaptation and cultural validation of the Self-confidence Scale in nursing students - Batista, Rui Carlos Negrão (2014)
Objective: develop the cultural adaptation and validation of a Portuguese version of the Self-confidence Scale. Method: descriptive and exploratory methodological research for the adaptation and validation of a measuring instrument. The translation, synthesis, back-translation, revision, pretest and semantic evaluation phases were accomplished. The evaluation involving 178 students from a Teaching Diploma Program in Nursing. The ethical principles were complied with. Results: the internal consistency analysis of the scale reveals good Alpha coefficients (0.92 for the global scale and superior to 0.83 for the different dimensions). The factor analysis presents a three-factor solution with rational meaning. Conclusion: The scale is easy to answer and understand. Based on the obtained results, it can be affirmed that the scale reveals good psychometric properties, with great potential to be used in future research.